Penggunaan Bio-Fertilizer Pada Tanaman Sayuran Petik Langsung untuk Menjaga Kehilangan Nutrisi Guna Mencegah Stunting Di Desa Semelit Mutiara - Khadijah, Khadijah; Syahfutra, Bayu Rahman; Tawardi, Tawardi; Saputra, Edi Eka (Universitas Gajah Putih, Indonesia, 2023)
Stunting is an irreversible growth disorder that can be influenced by many factors, one of which is influenced by insufficient nutrition. One of the efforts made to prevent stunting is to plant vegetable plants in the yard using biological fertilizer or biofertilizer. The use of biofertilizer does not cause residue and maintains the nutrients in the plants. So it is safe for consumption, both by pregnant women and babies or toddlers. Planting vegetable plants in the home garden using a biofertilizer will influence the amount and type of variation in nutritional intake for toddlers, thereby avoiding chronic malnutrition and stunting.